Kemuliaan Penjaga Lisan Dari Susut Pandang Hukum Islam - Juliana Anggraini; Nur Aisyah; Arizka Damayanti; M. Hadi Hidayat; Wismanto Wismanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
All aspects of human life can run smoothly because they follow established Islamic law. The law regulates in detail the aspects of rersubut because only matters of worship are regulated expressly in the law, the law also regulates matters relating to social life or muamalah which are given a legal basis with several important meanings and rah funds. for humans. The problem is that muamalah is assigned to humans. There are a number of legal principles to achieve certain aspects of human life. Islamic law was revealed to all mankind at one time and every moment until the miniature life ends on the Day of Judgment. Islamic law has a unique, universal and eternal nature. This is outside the proper worship of Allah SWT. We also have to be kind to other people, both in actions and words (speech), because words are a part of the human body that is quite small compared to other parts of the body but can cause sky-high losses. or it could even cause the owner to be thrown into hellfire. One should speak kind words that seem beneficial. If we suspect there is a problem, we should not make a sound because silence can be the first step to help us stay away from things that harm us. Because people who are good at keeping their mouths will occupy a high position in religion. Apart from that, other people are also protected from the dangers posed by our tombstones.